Infrared absorption spectra analysis of TeO2-ZnO-Bi2O3-TiO2 doped B2O3 glasses. (April 2020) - Fausta, Devara Ega; Marzuki, Ahmad; Cari,
Abstract: Boro-tellurite glasses with composition 60TeO2 - (30-x)ZnO- 5Bi2 O3 - 5TiO2 - xB2 O3 (where x = 0, 2.5, and 5 mol%) have been successfully fabricated by melt quenching technique. FTIR characterization was carried out in range 400-4000 cm −1 using a KBr pellet method to study the glass chemical bond. The results show that several absorption peaks were recorded in range 400-4000 cm −1 . However, most of the absorption peaks were detected in the region 400-1600 cm −1 . It can be divided into 5 groups from 400-450 cm −1, 620-650 cm −1, 900-940 cm −1, and 1100-1300 cm −1 . The main absorption peak of TZBT glass located at 620-650 cm −1, which is the fingerprint of TeO2 glass from Te-O vibration of TeO4 units. The addition of B2 O3 components constructed a new absorption at 930 cm −1 and 1100-1300 cm −1 . The absorption at 930 cm −1 belongs to B-O vibrations of BO4 units. While the absorption at 1100-1300 cm −1 relates to B-O vibrations of BO3 units. For further investigation, the deconvolution process was performed to discover the effect of the addition of B2 O3 in the main absorption spectra. It was confirmed that six bands detected in the main absorption peak. The effect of B2 O3 reduces the absorption band and shift the wavenumbers in TZBT glass.